Invisible ship tracks show large cloud sensitivity to aerosol - Manshausen, Peter; Watson-Parris, Duncan; Christensen, Matthew W.; Jalkanen, Jukka-Pekka; Stier, Philip (Nature (London), 2022)
Cloud reflectivity is sensitive to atmospheric aerosol concentrations because aerosols provide the condensation nuclei on which water condenses 1 . Increased aerosol concentrations due to human activity affect droplet number concentration, liquid water and cloud fraction 2 , but these changes are subject to large uncertainties 3 . Ship tracks, long lines of polluted clouds that are visible in satellite images, are one of the main tools for quantifying aerosol–cloud interactions 4 . However, only a small fraction of the clouds polluted by shipping show ship tracks 5 , 6 . Here we show that even when no ship tracks are visible in satellite images, aerosol emissions change cloud properties substantially. We develop a new method to quantify the effect of shipping on all clouds, showing a cloud droplet number increase and a more positive liquid water response when there are no visible tracks. We directly detect shipping-induced cloud property changes in the trade cumulus regions of the Atlantic, which are known to display almost no visible tracks. Our results indicate that previous studies of ship tracks were suffering from selection biases by focusing only on visible tracks from satellite imagery. The strong liquid water path response we find translates to a larger aerosol cooling effect on the climate, potentially masking a higher climate sensitivity than observed temperature trends would otherwise suggest. Investigations of the effect of aerosol emissions from shipping on cloud properties when both visible and invisible ship tracks are considered implies a large negative radiative effect (and associated cooling) from liquid water path adjustments.